Analysis of Overload Shedding (OLS) - Adaptive Defense Scheme (ADS) on The 150 KV Priok Subsystem to Enhance The Reliability of Jakarta's Electricity Supply In N-1 N-2 Contingency Scenarios - Randy, Mochammad Ali; Dalimi, Rinaldy (International Journal of Computer and Information System (IJCIS), 2025)
This study analyses the implementation of Overload Shedding (OLS) and Adaptive Defense Scheme (ADS) in the 150 kV Priok subsystem to enhance Jakarta’s electricity supply reliability under N-1/N-2 contingency scenarios. Using DigSILENT PowerFactory, the research evaluates system stability by modelling dynamic load responses, power flows, and contingency simulations. The objective is to optimize OLS-ADS parameters to mitigate cascading failures and ensure equipment safety during critical faults. The methodology involves detailed modelling of the Priok subsystem, including generators, transformers, and protective relays, validated via power flow analysis using the Newton-Raphson method. N-1/N-2 contingencies—such as tripping of IBT2/Bekasi, IBT1/Cawang, and dual IBT failures—are simulated to assess OLS-ADS performance. Dynamic load shedding logic adapts to real-time system conditions, prioritizing critical loads and generators. Results show that OLS-ADS successfully prevents equipment overloading in N-1 scenarios (e.g., IBT2/Bekasi tripping) by shedding 6–20% of the load, maintaining voltages (0.9–1.0 pu) and frequencies (49.9–50 Hz) within safe limits. Rotor angles in Priok’s PLTGU units remain below IEEE’s ±90° threshold. However, N-2 contingencies (e.g., simultaneous loss of IBT2/4/Bekasi) require shedding 50% of the load to avert cascading failures, highlighting systemic vulnerabilities. The study concludes that OLS-ADS significantly improves N-1 resilience but underscores the need for enhanced redundancy (e.g., integrating Muara Tawar’s 500/150 kV IBTs) to mitigate N-2 risks. Findings provide actionable guidelines for optimizing ADS logic and expanding grid infrastructure to ensure reliable power supply in DKI Jakarta